Evaluating Prehistoric Sea Ice Variability and Culture Change in Northwest Alaska. - Freeburg, Adam (2011)
Adam Freeburg, University of Washington, USA, at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.